Somatic Embryos Induction of East Kalimantan Local Rice (Oryza sativa L.) Cultivars and In Vitro Selection Against Salinity - Muktirianur Muktirianur; Bambang Supriyanto; Widi Sunaryo; Nurhasanah Nurhasanah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Soil salinity is one major environmental constraint on rice production, especially in coastal areas. The development of salt-tolerant genotypes is considered to be the most effective breeding strategy to overcome the constraint. This study aims to induce somatic embryos formation of East Kalimantan local rice cultivars and to obtain tolerant somatic embryos under saline condition via in vitro selection. Four commonly cultivated local rice cultivars, namely Buyung, Siam, Ketalun Tawar and Serai Gunung, were used in this study. The somatic embryos were produced using three different plant growth regulator (PGR) compositions. The salinity tolerance level of somatic embryos was induced by in vitro selection in salt toxicity medium containing 0 mM; 50 mM; 100 mM; 150 mM; 200 mM NaCl. The best medium for somatic embryogenesis contains 1 mg/l 2,4-D + 0.5 m/l BAP, resulting the highest percentage of cream and white non-compact callus on the tested cultivars. More than 70% of the somatic embryos were tolerant against salinity (NaCl 200 mM). However, only somatic embryos derived from Serai Gunung could regenerate into normal plantlets.